Laparotomy for Advanced Abdominal Ectopic Pregnancy - Dereje Tegene; Sultan Nesha; Befikadu Gizaw; Tadele Befikadu (Case Reports in Obstetrics and Gynecology)
Background. Abdominal pregnancy is the rarest and the most serious type of extrauterine pregnancy. The mainstay of treatment for advanced abdominal pregnancy is surgery. The fetus can be delivered easily, and there are two options for the management of the placenta: removal of the placenta and leave the placenta in situ. Case Presentation. This is a 26-year-old primigravida lady who does not recall her first day of last normal menstrual period (LNMP) but claimed to be amenorrhic for the past 9 months. She had antenatal care (ANC) follow-up at a private hospital and had obstetric ultrasound two times and told that the pregnancy was normal. Currently, she presented with absent fetal movement of one week and vaginal bleeding of 3 days duration. She had history of abdominal pain with fetal movement before one week. Upon examination, the abdomen was 34 weeks sized, with easily palpable fetal parts; fetal heartbeat was negative, with mild abdominal tenderness. The cervix was closed and uneffaced. She was investigated with ultrasound which reveals 3rd trimester abdominal ectopic pregnancy with negative fetal heartbeat. Laparotomy was done to deliver a 2000 gm female stillborn with GIII maceration from the peritoneal cavity. Placenta was removed after releasing adhesion from the bowel and omentum. She had smooth postoperative course and discharged on her 5th postoperative day. Conclusion. Abdominal ectopic pregnancy could be missed despite having repeated ultrasound scanning and may continue to third trimester. High index of suspicion and correlation of patient’s sign and symptom is very important to make early diagnosis.